THE ORIGIN, HISTORY OF DEVELOPMENT OF FREESTYLE WRESTLING AND METHODOLOGY OF RULES RELATED TO THIS SPORT - Khakimdjanova K. B.; Ergashev M. I. (Bright Mind Publishing, 2025)
This article provides information about the origin and development history of freestyle wrestling, the rules of this sport, instilling a sense of patriotism in the younger generation, and the philosophical foundations of this sport.
Keywords: Freestyle wrestling, Olympic Games, Physical training, National sport, International competitions.